Integrated diagnosis at the primary care level in Africa's low- and middle-income countries: What is it, what works, and for whom? A Realist Synthesis - Gwaza, Gamuchirai; Pluddemann, Annette; McCall, Marcy; Heneghan, Carl (Ubiquity Press, 2024)
Introduction Integrated diagnosis can improve health outcomes and patient experiences through early diagnosis and identification of cases that could otherwise be overlooked. While existing studies showcase the feasibility of integrated diagnosis across diverse conditions, a critical research gap exists regarding the conclusive link between integrated diagnosis at the primary care level and improvements in patient experiences and health outcomes. This review examines the conceptualizations of integrated diagnosis by various actors along the healthcare pathway in low- and middle-income countries (LMICs) and explores the necessary contexts and mechanisms crucial for its effectiveness. Methods This study adopts a realist methodology to comprehensively investigate integrated diagnosis. Employing a systematic approach, the research aims to collect, review, and synthesize existing evidence on integrated diagnosis, leveraging a program theory developed through literature review and expert discussions. Primary studies and reviews on integrated diagnosis, multi-disease testing, or integrated healthcare with a diagnostic component were sourced from key databases and global health organization websites. The collected evidence was used to build, refute, and test the evolving theoretical framework. Results This study identifies three models of integrated diagnosis interventions: individual/human resource integration, facility or mobile-based integration, and technology integration. The successful implementation of these models relies on an understanding of the values and perceptions of both healthcare workers and patients. This research emphasizes a holistic approach, considering all elements within the health system. Emphasizing a holistic methodology, the research underscores the interdependence of various elements within the health system. By framing contextual factors using the WHO health systems framework, the study positions diagnosis as an integral component of a broader health ecosystem. A key result of the research is the imperative to comprehensively address issues affecting integrated diagnosis interventions. This encompasses considerations such as policy frameworks, diagnostic tools, funding mechanisms, treatment pathways, and human resource management. To improve patient experiences, there is need to cultivate positive relationships with healthcare workers. This involves ensuring elements like respect, confidentiality, accessibility, and timeliness of services are considered. Despite integrated structures, there are potential challenges like increased waiting times that may impact patient uptake of integrated services. Discussion and Conclusion The diverse conceptualisations of integrated diagnosis highlight the necessity for clear definitions of each intervention, which is pivotal for the transfer of lessons, program comparisons, and effective measurement of results across different contexts. The success of integrated diagnosis is not a one-size-fits-all scenario; local contexts must guide decisions regarding the approach, conditions, and timing of integration to ensure sustainable outcomes. The review findings indicate that integrated diagnosis may be suitable at the primary care level in LMICs under specific circumstances. Successful implementation hinges on addressing both HCWs and patient perspectives, necessitating adequate time, resources, and a well-defined intervention model.
Keywords: Africa; Integrated diagnosis; Integrated Health Care; Primary health Care; Realist Review